2010
DOI: 10.1016/j.febslet.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A conserved gene cluster as a putative functional unit in insect innate immunity

Abstract: a b s t r a c tThe Nimrod gene superfamily is an important component of the innate immune response. The majority of its member genes are located in close proximity within the Drosophila melanogaster genome and they lie in a larger conserved cluster (''Nimrod cluster"), made up of non-related groups (families, superfamilies) of genes. This cluster has been a part of the Arthropod genomes for about 300-350 million years. The available data suggest that the Nimrod cluster is a functional module of the insect inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…NimC1 was initially identified as an antigen for the plasmatocyte specific monoclonal antibody P1. It belongs to the Nimrod gene family that has been implicated in the cellular innate immune response in Drosophila [46], [47]. A previous study pointed to the importance of NimC1 in the phagocytosis of bacteria, since RNAi-mediated silencing of this gene resulted in decreased S.…”
Section: Discussionmentioning
confidence: 99%
“…NimC1 was initially identified as an antigen for the plasmatocyte specific monoclonal antibody P1. It belongs to the Nimrod gene family that has been implicated in the cellular innate immune response in Drosophila [46], [47]. A previous study pointed to the importance of NimC1 in the phagocytosis of bacteria, since RNAi-mediated silencing of this gene resulted in decreased S.…”
Section: Discussionmentioning
confidence: 99%
“…NimC1 is also expressed in hemocytes, can bind E. coli, Serratia marcescens, Xanthomonas campestris, Pseudomonas aeruginosa and Bacillus cereus, and is involved in the phagocytosis of at least E. coli and S. aureus (Kurucz et al, 2007;Zsamboki et al, 2013). Members of this gene family have been identified in multiple insect orders, although their function has only been studied in detail in Drosophila (Ju et al, 2006;Kim et al, 2011;Somogyi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In D. melanogaster, a broad range of molecules have been reported to take part in this function, including the epidermal growth factor-like NIM repeatcontaining receptors, such as Eater, Draper and NimC1 [2][3][4]. We have previously shown that the NimC1 receptor, a member of the Nimrod protein family, is involved in the phagocytosis of bacteria [2] and proposed that the Nimrod gene cluster is a functional module in innate immunity [5]. Members of the Nimrod gene cluster are located in close proximity to each other in the Drosophila genome and a number of them are up-regulated in response to an immune challenge, suggesting their co-regulation in the course of the innate immune response [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the NimC1 receptor, a member of the Nimrod protein family, is involved in the phagocytosis of bacteria [2] and proposed that the Nimrod gene cluster is a functional module in innate immunity [5]. Members of the Nimrod gene cluster are located in close proximity to each other in the Drosophila genome and a number of them are up-regulated in response to an immune challenge, suggesting their co-regulation in the course of the innate immune response [5,6]. Nimrod proteins contain a signal peptide, 1-16 characteristic EGF-like domains, called NIM domains, which have a well-conserved consensus sequence [2], and a short conserved CCxGY motif, immediately preceding the first NIM domain.…”
Section: Introductionmentioning
confidence: 99%